When to search for birth care: mothers narratives - Reis Queiroz, Jessica; Komura Hoga, Luiza Akiko; Goulart Gonçalves, Bruna (Investigación y Educación en Enfermería, 2016)
Objective. The aim of this study was to describe the experiences lived by the pregnant woman on the decision-making process about the time to go to the hospital, to ask for childbirth care. Methods. The narrative analysis was the research method. The thematic analysis of the narratives was performed and the descriptive categories (DCs) were validated by study participants. Results. Two DCs to reveal the collective experience: "Receiving guidance, social support and making choices: planning the going to the hospital" and "Between the planned and the unpredictable: decision process about the time to go to the hospital". Conclusion. The decision-making process of women is reasoned especially on the social support network, and also on the advises received from healthcare providers. The professionals involved in prenatal care should develop actions considering the pregnant women’s social context, and the family members should be integrated in the provision of prenatal care. The adoption of these measures is essential for the improvement of the quality of care. How to cite this article: Reis-Queiroz J, Hoga LAK; Gonçalves BG. When to search for birth care: mothers narratives. Invest Educ Enferm. 2016; 34(1): 162-170